Improved-performance digital holographic microscopy (2018)
The present thesis of Doctorate in Sciences - Physics (PhD in Physics) focuses on the improvement of the performance of digital holographic microscopy (DHM) in its different versions. To increase the performance of this microscopy technique, new experimental essays and optical elements were developed and/or implemented to obtain phase information, new autofocusing algorithms of holographic reconstructions were designed, a numerical darkfield illumination was implemented in lensless DHM to enhance the contrast of the reconstructions and image processing algorithms were applied over holograms and its reconstructions to improve the information provided by this imaging technique. The scientific and technological interest of the project underlies the fact that DHM has multiple applications in fields such as medicine, biology, computer security, materials science, fluid analysis, among other areas, and the improvements presented in this thesis will expand its field of application. Among the expected results of this project were achieved: i) the improvement of the DHM from the topics mentioned above, ii) the publication of scientific articles and presentations in events related to the topic with global recognition, iii) the registration of the software developed during this research, and iv) a granted patent. Attached to this text can be found the 9 papers reported during this research which constitute the core of this PhD thesis.